A nominalização como estratégia de relativização em línguas nativas da Amazônia brasileira - Camacho, Roberto Gomes [UNESP] (My University, 2012)
This work aims to present some results obtained from a typological research project on relative clauses developed in a sample of Amazonian native languages. These results, which specifically address the distribution of the relativization strategies in the sample, intend to show, on one hand, that the use of nominalization is in fact a compensatory strategy and, on the other hand, that some languages, which use nominalization as a primary strategy of relativization, lack a specific class of adjectives.
Keywords: estratégias de relativização